Note on Energy Transfer of Jeffrey Fluid Flow on Mixed Convection in Prasence of Chemical Reaction Parameter - Shreedevi Kalyan (International Journal of Advanced Science and Technology)
A Mixed convective flow of energy transfer by Jeffrey flow with Newtonian fluid is studied. A Mathematical model is analytically solved using regular perturbation method. The influence of the different parameters and inclination angle are discussed through the graphical representations. It is observed that the consequences of Jeffrey fluid parameters have been noted, also the physical behaviour of Jeffrey fluid has been presented graphically, presence of Jeffrey on velocity and temperature fields enhances the fluid flow. The role of chemical reaction parameter is to show demotivational effect on the flow. These results are having lot of applications in chemical and engineering fields. Validity of our work holds good agreement with the result obtained from Pratapkumar et al.[36] in absence of Jeffrey fluid and Sreenad et.al.[23] in presence of Jeffrey fluid.